O ritual simbólico do Ctrl+C (copiar ) e Ctrl+V (colar) no ensino médio - Amorim, Corina de Sá Leitão (2012)
Nowadays, technology has a direct influence on the relationship student and teacher have with language. The internet is a powerful tool in helping work with the language and, through it, the knowledge comes to the student easily and intensely. Furthermore, this facility has enhanced and made visible what has been called, within the University community, "plagiarism generation." This work assumes that this generation has, in their written texts, symbolic movements similar to those of "copy and paste" applied to research work carried out by high school students. Taking this as starting point, this dissertation aims to analyze how high school students of the 1st year from a school in Natal (RN) construct texts, under the movements known as "Ctrl + c" and "Ctrl + v", with reference to the text of the "other". More specific issues are behind the general objective, namely: 1. how the student appropriates the source-text when he copies and pastes? 2. What are the categories of analysis that allow us to look analytically and theoretically for the "ctrl + c / ctrl + v" practice made by the student? 2. how the studies developed in the fields of "Genetic Criticism" (Grésillon, 1987), the "school manuscripts" (Calil, 2004) and "paraphrase" (Fuchs, 1982) may help in working with writing in the classroom standing as a possible way to minimize the copy and paste effects in the students texts? Thus, we observe the categories of analysis that allow us to look, theoretically and analytically, for the symbolic ritual of the "ctrl + c" (copy) and "ctrl + v" (paste) in high school. Our study shows that the student text is a "hybrid body" whose writing is a drawing entanglement because of the presence of the foreign text, verbatim, and the presence of linguistic elements to paraphrase the original text.This textual embodiment has, behind it, certain operations, namely: replacing, moving, adding and deleting statements. Given the specificity of the data and the research objectives, this study aligns with qualitative research methods (SILVERMAN, 2009) and falls within the knowledge field of Applied Linguistics, which is characterized especially by investigating problems, phenomena in which language in a real situation is taken as central (BRUMFIT, 1995).Theoretically, our work follows the approach of studies on the paraphrase (Fuchs, 1982, 1994a, 1994b; DAUNAY, 1997, 1999, 2002a, 2002b), the studies developed in the field of Genetic Criticism (Grésillon, 1987, 1994, 1992, 2008 ) and those developed by Eduardo Calil (2004) on "school manuscripts"